Osnovi ! gradniki kondicijske priprave boksarja - Korsika, Žiga (Šport (Ljubljana), 2014)
The purpose of this article is to introduce a view on boxing, based on biomechanical and physiological analysis of movement with the help of expert literature It highlights the more important aspects of load and effort, which include endurance, power and speed, that suggest a way in which boxers should supplement technical-tactical training in order to better their competitive ability.
Keywords: boks; borilne veščine; borilni športi; boxing; combat sports; conditioning; gibalne sposobnosti; kondicijska priprava; martial arts; motor skills; sport; šport; športna dejavnost; training; trening